PEG-4000 increased the mating efficiency of yeast-two hybrid screening process using PmF-box1 as bait - Nur Athirah Abd Hamid,; Ismanizan Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Protein degradation can occur through Ubiquitin 26S-Proteosome System (UPS). The degradation can be mediated by the SCF E3 ubiquitin ligase complex consisting of Skp1, Cullin, and F-box protein as the main components. The F-box protein at the C-terminal domain functions to recognize the targeted protein to be ubiquitinated and degraded via UPS. A stress-responsive F-box gene, PmF-box1 from Persicaria minor was categorized in the F-box containing kelch repeat (FBK) family; a family that specific to plant kingdom. To identify the targeted protein of PmF-box1, yeast-two hybrid system (Y2H) was used. In the Y2H screening process, mating efficiency is very important to fish out the interacting proteins. Therefore, one modification was conducted to increase the mating efficiency. In this screening, PmF-box1 was used as a bait to screen for the Y2H library which was constructed using RNA from plant samples treated with abscisic acid (ABA) and polyethylene glycol (PEG)-8000 and control sample. Autoactivation and toxicity tests of bait were performed before the Y2H screening. Tests on PmF-box1 showed that it is not toxic to the yeast and cannot autoactivate the yeast reporter genes. Mating efficiency was improved from 2.07% to 9.15% after addition of PEG-4000 in the mating culture compared to the original protocol, which it also increased the colony number in the screening step afterward. Additionally, bands of gene with different sizes were observed on electrophoresis gel after colony PCR analysis from the improved technique. Those genes may code for potential interacting proteins that needs further identification and confirmation.